Security of the deployment of SDN-based IoT using blockchain - Ping XIE; Xiaosong LIU (Dianxin kexue)
Compared with the traditional internet,the SDN-based internet of things (IoT) has a wider coverage,more connected devices,more complex data transmission.There are many security technical challenges.The security challenges of SDN-based IoT deployment were firstly analyzed,and then the advantages of blockchain technology in solving those security issues were introduced.Finally,to add a blockchain-based security layer was proposed,which acted as a security gateway,data entering the IoT was verified accurately one time.Each security gateway was added to the blockchain system as an equal blockchain node,combined with the traceability and non-tampering of the blockchain system,the security performance and efficiency of SDN-based IoT deployments was improved.